NUTQI TO‘LIQ RIVOJLANMAGAN MAKTABGAChA YOShDAGI BOLALAR BILAN KORREKSION-RIVOJLANTIRUVChI IShLARDA LOGOPEDIK RITMIKANING AHAMIYATI - Tajimuratov, A.J. (SCIENCE and SOCIETY, 2025)
The article presents the results of theoretical and empirical studies on the pathogenetic mechanism of general speech underdevelopment, as well as an original system of logorhythmic intervention developed by the author. The effectiveness of using logopedic rhythmics as part of a comprehensive corrective and developmental approach is analyzed to overcoming general speech underdevelopment in younger preschool children.